TRANSFORMATION OF INDONESIAN SEA TRANSPORTATION AND MARITIME LOGISTICS TO REALIZE THE VISION OF GOLDEN INDONESIA 2045 - K.P.Suharyono S.Hadiningrat; Bahana Wiradanti; Yusuf Ferdian Umar (Yayasan Inspirasi Merah Putih Indonesia, 2024)
As a large archipelago country, Indonesia envisions to become a